Purchase Intention: Can Brand Awareness Mediates Online Consummer Reviews? - Susilowati, Heni; Titin Hargyatni (STEKOM PRESS, 2021)
This study aims to determine the effect of Online Consumer Review on Purchase Intention with Brand Awareness as an Intervening Variable at Shopee into STEKOM University’s students. The primary data was obtained by distributing questionnaires to buyers who have shopped at Shopee which consists of 23 questions. Samples of 130 respondents taken by random sampling technique. The analytical tool used in data processing uses Multiple Linear Regression with the help of SPSS version 25. The results show that Online Consumer Reviews ( Online Reviews on Website, Consistency of Online Reviews and Website Popularity) have a positive effect on brand awarensess at Shopee. Online Consumer Reviews (Online Reviews on Website, Online Consistency of Reviews and Popularity of Website) variables also have a positive and significant effect on Purchase Intention. Meanwhile, the Brand Awareness variable is not able to mediate Online Consumer Reviews on Purchase Intentions at the Shopee shopping platform.